Antibiotic-laden bone cement for diabetic foot infected wounds: A systematic review and meta-analysis - Dong, Tingting; Huang, Qi; Sun, Zengmei (Frontiers in Endocrinology, 2023)
Objective A large body of literature has demonstrated the significant efficacy of antibiotic bone cement in treating infected diabetic foot wounds, but there is less corresponding evidence-based medical evidence. Therefore, this article provides a meta-analysis of the effectiveness of antibiotic bone cement in treating infected diabetic foot wounds to provide a reference basis for clinical treatment. Methods PubMed, Embase, Cochrane library, Scoup, China Knowledge Network (CNKI), Wanfang database, and the ClinicalTrials.gov were searched, and the search time was from the establishment of the database to October 2022, and two investigators independently. Two investigators independently screened eligible studies, evaluated the quality of the literature using the Cochrane Evaluation Manual, and performed statistical analysis of the data using RevMan 5.3 software. Results A total of nine randomized controlled studies (n=532) were included and, compared with the control group, antibiotic bone cement treatment reduced the time to wound healing (MD=-7.30 95% CI [-10.38, -4.23]), length of hospital stay (MD=-6.32, 95% CI [-10.15, -2.48]), time to bacterial conversion of the wound (MD=-5.15, 95% CI [-7.15,-2.19]), and the number of procedures (MD=-2.35, 95% CI [-3.68, -1.02]). Conclusion Antibiotic bone cement has significant advantages over traditional treatment of diabetic foot wound infection and is worthy of clinical promotion and application. Systematic review registration PROSPERO identifier, CDR 362293.